Penguatan Literasi Digital untuk Meningkatkan Kerukunan Antarumat Beragama - Eko Nani Fitriono; Dedi Gunawan Saputra (Yayasan Syamil Quran Nunukan, 2024)
Indonesia is a country rich in diversity, including in terms of religion. This diversity has the potential to be a force that strengthens national unity, but on the other hand it can cause conflict if not managed well. In the digital era, technology provides a great opportunity to strengthen religious harmony through strengthening digital literacy. Digital literacy is the key to increasing tolerance, equality and cooperation between religious communities by using digital space wisely. This research aims to examine the role of digital literacy in building religious harmony in Indonesia. The method used is a qualitative-descriptive approach with data collection techniques in the form of in-depth interviews, participatory observation and document analysis. The research results show that digital literacy plays an important role in supporting positive interactions in the digital realm, reducing the potential for conflict between religious communities, and encouraging constructive interfaith dialogue. However, people's digital literacy level still needs to be increased to minimize the spread of hoaxes and negative information that can trigger intolerance. Therefore, a strategy to strengthen digital literacy is needed through education, training and social campaigns involving various parties. This research concludes that digital literacy is a strategic element in realizing religious harmony in the digital era. With the appropriate use of technology, digital literacy can be a means of strengthening unity and harmony in the life of a multicultural society.